Multigrid solution of Euler equations using high-resolution NVD differencing scheme for unstructured meshes - Ng K.C.; Yusoff M.Z.; Ng E.Y.K. (Inderscience Publishers, 2023)
High-speed compressible flows in a nozzle and over an airfoil have been computed by solving the Euler equations using the GAMMA differencing scheme for spatial discretisation on unstructured grid. This high-resolution technique originally developed in a segregated algorithm has now been modified for the present coupled solver by introducing a non-linear blending factor to enhance its convergence property while preserving the Total Variation Diminishing (TVD) criterion. The efficiencies of the GAMMA scheme and its variant have been augmented with a novel agglomeration multigrid scheme to accelerate the convergence to steady state using the multi-stage Runge-Kutta time-marching technique. Copyright 2006 Inderscience Enterprises Ltd.